Migration departure strategies of shorebirds at a final pre-breeding stopover site - Tan, Kun; Choi, Chi-Yeung; Peng, Hebo; Melville, David S.; Ma, Zhijun (Avian Research, 2018)
Background: Departure decisions and behaviors of migratory birds at stopover sites are expected to maximize fitness by trade-offs among avoiding predators, optimizing refueling (energy) capacity, and matching other life-history events. We predict that species with different body sizes and migratory destinations will exhibit different behaviors when departing from the same stopover site. We also predict that with strong time constraint at the final pre-breeding stopover site, departure decisions may be less sensitive to exogenous factors, such as wind condition, compared to other stopover or nonbreeding sites. Methods: We recorded migratory departures of four shorebird species, i.e. Eurasian Curlew (Numenius arquata), Bar-tailed Godwit (Limosa lapponica), Great Knot (Calidris tenuirostris), and Grey Plover (Pluvialis squatarola), at Yalujiang Estuary Wetlands in China, a final pre-breeding stopover site in the northern Yellow Sea, from 2011 to 2014. We compared flock sizes, departure time and departure directions between species, and investigated the effects of tide and weather conditions (rain and ground wind speed and direction) on the departure decision of shorebirds. Results: We found that larger species departed in smaller flocks and were more variable in daily departure time. Departure trajectory of all four species appeared to be influenced by coastal topography. With the east-west coastline and intertidal mudflat on the south, birds exhibited westward or eastward deflection from the shortest migratory routes. Bar-tailed Godwit was the only species that deviated to the southeast and did not climb over the land. Birds avoided departure during precipitation, while their departure was not related to ground wind benefit or tidal condition. Conclusions: Body size among species, which influences their vulnerability to predators, might be important in shaping shorebird departure strategies. Diverse departure directions could be the result of different wind use tactics in climbing stage. Narrow optimal time window of breeding might lead to reduced flexibility in departure date at a final pre-breeding site. Both endogenous and exogenous are important in shaping departure behaviors and decisions.